Mobile Application Design History Tourism Bandung City - Anto Purwanto; Dwinita Larasati; Banung Grahita (International Journal of Education, Information Technology, and Others, 2023)
Bandung leaves many historic buildings, with 418 historic buildings protected under the local regulations of the City of Bandung. This can be evidence of the existence of culture and character possessed by the City of Bandung as a city that has high historical value and makes Bandung one of the historical tourism destinations. This attraction is what makes tourists arrive in the city of Bandung. Even one of them underlies the existence of activists or tourist communities who use historical themes in the city of Bandung. But the lack of historical information makes tourists who come to the city of Bandung not aware of the existence of historical values ​​and historical tourism patterns in Bandung. The variety of tourist activities and historical tourism information as well as its historical value are interesting themes to be appointed as a source of ideas for designing historical tourism information designs in Bandung. This study uses a human centered design approach that begins with observing and interviewing, namely conducting interviews with tourists and the Bandung historical community about the knowledge and patterns of tourism or historical tour experiences in the city of Bandung. Then Ideation is the stage to produce alternative solutions that are raised to the target user that is making a media that can be a guide or tour guide with mobile media applications. Next prototyping is the stage of making a visual appearance of mobile applications and augmented reality technology compiled using elements of user experience Next to be tested, namely testing the target user of mobile applications with usability test. The results of the study are in the form of a mobile application design containing a guide or guide and additions to the tour experience with augmented reality technology for tourists who come to the historical attractions of the city of Bandung